(untitled) (Ukrainian Journal of Ophthalmology, 2025)
Aim. To determine the influence of a biocomposite on the state of the immune system of patients with trauma to the frontal bone at 1 month after surgical treatment. Materials and Methods. 20 patients with frontal bone fracture treated surgically with and without a SYNEKIST biocomposite were examined; 10 patients served as control. Immunoglobulins M, G, A, and E were determined in the blood serum using enzyme-linked immunosorbent assay. We also determined the content of prodefensin (lactoferrin, an indicator of the acute phase of inflammation), interleukins IL-1?, and interleukin-10. Results. On presentation and during the first days, the patients with trauma to the frontal bone had a decreased level of IgM which, however, reached the control level and was practically the same in both groups. There were no changes in other immunoglobulins in a month. The level of pro-inflammatory Il-a was increased on admission with a significant decrease within the first month in both treatment approaches. The on-admission level of pro-inflammatory cytokines did not differ significantly from the control while its level increased in the patients undergone the surgical treatment using a biocomposite material. The level of lactoferrin decreased to normal ranges in both treatment approaches. Conclusions. The advantage of the surgical treatment using a biocomposite material lies in the restoration of the IgM level and activation of anti-inflammatory mechanisms, Il-10, in particular, in 1 month.